Construction of systemic interaction between tools of remote monitoring of the technical condition and operation modes of a truck vehicle - Gritsuk, Igor; Khudiakov, Igor; Volodarets, Mykyta; Pohorletskyi, Dmytro; Pohorletska, Nadiia; Ukrainskyi, Yevhen; Petrov, Igor; Nosov, Pavlo; Tazhenov, Askar; Litvinov, Mikhaylo (Eastern-European Journal of Enterprise Technologies, 2024)
Parameters of the technical condition of transportation means in modern transport-logistics and infrastructure systems are an integral element of their communication support. This is enabled by the use of remote information monitoring technologies in control processes. The object of this study is the processes of vehicle remote monitoring in terms of determining the technical condition. The work addressed the task of improving the process of vehicle technical operation through the construction of a model of the remote monitoring system of its technical condition. A remote version of the information-analytical monitoring system was implemented. The work considers the system interaction of the means of remote monitoring of the state of a vehicle to ensure control under the operating conditions of the driver’s work and rest modes. Road, transport, climatic conditions, etc. were taken into account. Considering these features, an information and analytical model of the system for remote monitoring of vehicle condition was built. Features of the subject area of the system are described using a DFD diagram. A structured information model of the information-communication system has been constructed, which has the ability to actually provide vehicle remote monitoring, the driver’s work and rest modes, and his/her physical condition. The results, subject to the use of the V2I information model in the field of transport, allow remote monitoring of the vehicle technical condition. Specifically, to analyze the influence of changes in the physical condition and modes of work and rest of drivers on changes in the vehicle operating parameters